2014
DOI: 10.1371/journal.pone.0103563
|View full text |Cite
|
Sign up to set email alerts
|

Bone Morphogenetic Protein 15 in the Pro-Mature Complex Form Enhances Bovine Oocyte Developmental Competence

Abstract: Developmental competence of in vitro matured (IVM) oocytes needs to be improved and this can potentially be achieved by adding recombinant bone morphogenetic protein 15 (BMP15) or growth differentiation factor (GDF9) to IVM. The aim of this study was to determine the effect of a purified pro-mature complex form of recombinant human BMP15 versus the commercially available bioactive forms of BMP15 and GDF9 (both isolated mature regions) during IVM on bovine embryo development and metabolic activity. Bovine cumul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
39
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 68 publications
(92 reference statements)
6
39
0
1
Order By: Relevance
“…3). These results are entirely consistent with our recent observation that pro-BMP15, but not mature domain BMP15 nor mature domain mouse GDF9, enhances oocyte developmental competence (54,55). It is well established that prodomains of TGF-␤ superfamily growth factors have important roles in protein folding and regulation of bioactivity (56,57).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…3). These results are entirely consistent with our recent observation that pro-BMP15, but not mature domain BMP15 nor mature domain mouse GDF9, enhances oocyte developmental competence (54,55). It is well established that prodomains of TGF-␤ superfamily growth factors have important roles in protein folding and regulation of bioactivity (56,57).…”
Section: Discussionsupporting
confidence: 92%
“…We and others have shown that addition of "native" oocyte-secreted factors (e.g. pro-BMP15 or pro-GDF9) to IVM enhances oocyte quality, having profound effects on embryo development and fetal survival (13,54,55,(61)(62)(63)(64). This study is the first report on the effects of cumulin on oocyte quality.…”
Section: Discussionmentioning
confidence: 63%
“…In the present study we used human B15 and human G9 proteins in their full-length pro-mature forms, which importantly are the forms needed to enhance oocyte developmental competence, including in AREG-induced IVM (Hussein et al, 2006;Sudiman et al, 2014b;Sugimura et al, 2014). By contrast, the truncated mature domains of B15 and G9 do not enable EGF-stimulated expansion of COCs from small antral follicles and also do not appear to contribute to oocyte developmental competence (Sudiman et al, 2014a), the possible mechanisms of which are discussed elsewhere (Sudiman et al, 2014b). In addition, human B15 þG9 can activate not only SMAD1/5/8 and SMAD2/3, but also non-SMAD signaling pathways (Reader et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Compact COCs with greater than 3 layers of cumulus cells and a homogeneous ooplasm were cultured in porcine oocyte medium containing 3 mg/ml polyvinyl alcohol (POMþ PVA) (Yoshioka et al, 2008), and depending on the treatment: supplemented with or without standard porcine oocyte in vitro maturation (IVM) doses of gonadotropins (Gns) consisting of 10 IU/ml equine chorionic gonadotropin (Folligon, Intervet, Bendigo, Australia) and 10 IU/ml human chorionic gonadotropin (Organon, Sydney, Australia) or; 0-500 ng/ml recombinant human amphiregulin (AREG; R&D Systems, Minneapolis, MN, USA), in the presence or absence of 1 mmol/L dibutyryl cAMP (cAMP) (Funahashi et al, 1997); 100 ng/ ml recombinant human GDF9 (G9); 100 ng/ml recombinant human BMP15 (B15); or B15 þG9, for 22 h at 38.5°C in a highly humidified atmosphere of 5% CO 2 in air. After 22 h COCs were washed and then transferred into the same medium but without gonadotropins, AREG, B15, G9 or cAMP for an additional 22 h. G9 and B15 were produced in our laboratory as concentrated preparations of pro/mature-region complexes, produced in 293 T cells, as previously described (Pulkki et al, 2011(Pulkki et al, , 2012, and as described as supplements to oocyte IVM medium at the same doses as used here (Li et al, 2015;Sudiman et al, 2014b;Sugimura et al, 2014). Ten COCs were incubated in 100 ml of IVM medium, covered with paraffin oil in 35-mm Petri dishes.…”
Section: Oocyte Collection and In Vitro Maturationmentioning
confidence: 99%
“…Finally, the protein used for the above-mentioned granulosa cell studies consists of only the mature region of the protein, and we have recently shown that the purified mGDF9 mature region is not active in stimulating oocyte developmental competence (40). We have also shown for human BMP15 that the protein needs to be present as the purified pro-mature complex form to stimulate oocyte developmental competence (73). Hence, in our experiments, we have used the purified pro-mature complexes of hGDF9 and the related mutants.…”
Section: Discussionmentioning
confidence: 99%